Comparison of Airway Management Success Using Video Laryngoscopy in Patients with Difficult Airways - Khurram Liaqat, Farah Naz, Iram Shahzadi, Sayed Makarrom Bukhari, Safeer Butt, Asad Ahmed Sheikh (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Difficult airway management is a critical component of anesthetic and emergency care. Objective: This study compared the success and safety of video laryngoscopy and direct laryngoscopy in patients with difficult airways. Methods: A comparative cross-sectional study was conducted at Pakistan Institute of Medical Sciences (PIMS), Islamabad from November 2022 to April 2023, on 105 patients with anticipated or encountered difficult airways. Of these, 53 patients underwent video laryngoscopy and 52 underwent direct laryngoscopy. Data included first-pass success, total intubation attempts, intubation time, Cormack–Lehane grading, need for adjuncts, and airway-related complications. Results: Video laryngoscopy achieved a higher first-pass success rate of 84.9% (45 of 53) compared with 57.7% (30 of 52) in the direct laryngoscopy group. The mean intubation time was shorter with video laryngoscopy at 28.6 ± 9.4 seconds, whereas direct laryngoscopy required 39.7 ± 12.3 seconds. Better glottic visualization was observed with video laryngoscopy, with 83.0% achieving Cormack–Lehane grades I–II compared with 48.0% in the direct laryngoscopy group. Adjunct use was lower in the video laryngoscopy group at 17.0% compared with 46.1% in the direct laryngoscopy group. Complications were fewer with video laryngoscopy, including desaturation in 7.5% versus 23.0%, airway trauma in 5.6% versus 17.3%, and esophageal intubation in 1.9% versus 9.6% in the direct laryngoscopy group. Conclusion: Video laryngoscopy proved superior to direct laryngoscopy in the management of difficult airways. It resulted in higher intubation success, better visualization, fewer complications, and reduced dependency on operator skill. Keywords: Laryngoscopy, Patients, Complications, Airway, Anesthetic, Incubation